Coupling the heating and power sectors: The role of centralised combined heat and power plants and district heat in a European decarbonised power system - Jiménez-Navarro, Juan-Pablo; Kavvadias, Konstantinos; Fillippidou, Faidra; Pavičević, Matija; Quoilin, Sylvain (Elsevier, 2020)
This work examines the role of centralised cogeneration plants as one of the potential pathways of a future decarbonised energy system. Even in this context, thermal power plants will still exist and the utilisation of their excess heat via district heating networks can assist the decarbonisation of the built environment. In particular, the potential of existing thermal power plants to operate as combined heat and power (CHP) plants is assessed and their impact on the power system quantified. To do so, the European heat demand for the built environment is described, focused on the heat demand supplied with fossil fuels, and the European power sector is discussed. Then, a power system model (Dispa-SET) is used to evaluate this coupling pathway in terms of operating costs, efficiencies and associated CO2 emissions. The analysis is developed for the current and future European power system. Results show that the conversion of thermal into CHP plants increases the efficiency and reduces both the operating costs and the environmental impact of the energy system. Not only that, it also offers alternative flexibility options when coupled with thermal storage. Still, large investments regarding the deployment of thermal networks are required to leverage the full CHP potential.
Keywords: Cogeneración de energía eléctrica y térmica; Calefacción urbana; European sector coupling; Power sector; Heat and power; Long term decarbonisation